2010
DOI: 10.1007/s12253-010-9298-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Functional MRI Information into Radiotherapy Planning of CNS Tumors-Early Experiences

Abstract: The purpose of our study was to examine the integration of functional MRI (fMRI) information into 3D based planning process of the central nervous system (CNS) malignancies. Between 01.01.2008 and 01.12.2008 four patients with astrocytoma were enrolled to this study. Before the planning process conventional planning CT, postoperative MR and individual functional MRI examinations were delivered. For the functional MRI examination the following four types of stimulus were applied: acoustic, visual, somatosensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Our initial experiences of fMRI-based treatment planning of CNS tumours were published after a feasibility study (experiments based on data from four patients) [4].…”
Section: Background and Purposementioning
confidence: 99%
“…Our initial experiences of fMRI-based treatment planning of CNS tumours were published after a feasibility study (experiments based on data from four patients) [4].…”
Section: Background and Purposementioning
confidence: 99%
“…This includes cumulative (RMS.scan, RMS.task, and RMS.rest) and statistical (RMS.diff, RMS.dyn) parameters. After a correlation analysis between patients' physiological scores and motion parameters (7), we have selected RMS.diff to represent intersubject motion variability in the corrected population-level model (STIM + RMS.diff) (8). REG = registration-based motion correction; M6 = six motion parameters; CompCor = component-based noise correction; STIM = stimulus group-mean model; RMS = root-mean-squared; RMS.scan = total displacement through the session; RMS.task = movement during task; RMS.rest = movement during rest; RMS.diff = statistical difference between head motion during active and passive periods; RMS.dyn = ratio of movement in task and rest periods; ROI = region of interest; FLIRT = FMRIB's Linear Image Registration Tool.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Noninvasive mapping of brain activity with blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) has become a key technology in many clinical fields, including neuropsychology, 4 neurororadiology, 5 neurosurgery, 6 and radiotherapy. 7 It also has a major role in evaluating poststroke recovery and rehabilitation 8,9 and in investigating the relationship between neural reorganization and functional recovery after stroke. 10 In stroke rehabilitation, the poststroke motor dysfunction and the corresponding potential cerebral reorganization can be characterized by using active and passive movement-based fMRI experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In a feasibility study of 4 patients with low-grade glioma, Kovacs et al co-registered fMRI following acoustic, visual, somatosensory and numeral stimuli to a planning CT scan (89). The study showed that with fMRI based 3D conformal planning, radiotherapy dose to the superior and inferior temporal gyrus and lingual gyrus could be reduced by an average of 50%.…”
Section: The Potential For Integrating Modern Imaging With Novel Radimentioning
confidence: 99%